Mediterranean-Style Diet Effect on the Structural Properties of the Erythrocyte Cell Membrane of Hypertensive Patients: The Prevencion con Dieta Mediterranea Study - Barceló, Francisca; Perona, Javier S.; Prades, Jesús; Funari, Sérgio S.; Gomez-Gracia, Enrique; Conde, Manuel; Estruch, Ramon; Ruiz-Gutiérrez, Valentina (Hypertension (Dallas, Tex. 1979), 2009)
A currently ongoing randomized trial has revealed that the Mediterranean diet, rich in virgin olive oil or nuts, reduces systolic blood pressure in high-risk cardiovascular patients. Here, we present a structural substudy to assess the effect of a Mediterranean-style diet supplemented with nuts or virgin olive oil on erythrocyte membrane properties in 36 hypertensive participants after 1 year of intervention. Erythrocyte membrane lipid composition, structural properties of reconstituted erythrocyte membranes, and serum concentrations of inflammatory markers are reported. After the intervention, the membrane cholesterol content decreased, whereas that of phospholipids increased in all of the dietary groups; the diminishing cholesterol:phospholipid ratio could be associated with an increase in the membrane fluidity. Moreover, reconstituted membranes from the nuts and virgin olive oil groups showed a higher propensity to form a nonlamellar inverted hexagonal phase structure that was related to an increase in phosphatidylethanolamine lipid class. These data suggest that the Mediterranean-style diet affects the lipid metabolism that is altered in hypertensive patients, influencing the structural membrane properties. The erythrocyte membrane modulation described provides insight in the structural bases underlying the beneficial effect of a Mediterranean-style diet in hypertensive subjects.